Preparation method of modified In2O3 and thermoplastic resin composite material containing modified In2O3

By adding modified In2O3 to the thermoplastic resin, the problems that existing thermoplastic resins cannot meet in areas with high mechanical properties are solved, and the mechanical properties of thermoplastic resins are significantly improved and the application fields are expanded.

CN119529387AInactive Publication Date: 2025-02-28HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311087597.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing thermoplastic resins cannot meet some application areas with high mechanical properties, which limits their application in these areas.

Method used

By preparing the modified In2O3 and adding it to the thermoplastic resin, the compatibility of the thermoplastic resin and In2O3 is improved, and the mechanical properties of the thermoplastic resin are improved by forming a three-dimensional mesh crosslinking structure.

Benefits of technology

It significantly improves the mechanical properties of thermoplastic resins and expands its application range in applications with high mechanical properties requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004416584220000041
    Figure BDA0004416584220000041
  • Figure BDA0004416584220000051
    Figure BDA0004416584220000051
Patent Text Reader

Abstract

The invention discloses a preparation method of modified In2O3 and a thermoplastic resin composite material containing the modified In2O3, nano In2O3 is modified, so that the compatibility between the nano In2O3 and thermoplastic resin is improved, and the mechanical property of the thermoplastic resin composite material is improved; and a three-dimensional network cross-linked structure formed in the modified In2O3 can further improve the mechanical properties of the thermoplastic resin composite material. The obtained thermoplastic resin composite material has excellent mechanical properties, can be used in the fields of automobile and household appliance materials, and has excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials and specifically relates to a modified In 2 O 3 The preparation method also relates to a modified In 2 O 3 The thermoplastic resin composite material has excellent mechanical properties. Background Art

[0002] Thermoplastic resin is a widely used polymer polyester resin that softens when heated and hardens when cooled. It does not react chemically and maintains this property no matter how many times it is heated and cooled. All thermoplastic resins have a linear molecular structure. It includes all polymerized resins and partially condensed resins. Although existing thermoplastic resins have advantages such as good fatigue resistance, good heat resistance and excellent dimensional stability, in some specific application fields, such as fields that require high mechanical properties of thermoplastic resins, current thermoplastic resins cannot meet the application requirements, which limits the application of thermoplastic resins in these fields. Summary of the invention

[0003] In view of this, the present invention provides a modified In 2 O 3 The preparation method of the modified In 2 O 3 Adding it to thermoplastic resins can give them excellent mechanical properties, which is of great significance for expanding the application areas of thermoplastic resin materials.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] The present invention first provides a modified In 2 O 3 The preparation method comprises the following steps:

[0006] Take nano-In 2 O 3 , AC-201, anhydrous ethanol and deionized water, react in a water bath at 40-60°C for 10-16h to obtain Indium ions treated with titanate coupling agent AC-201 2 O 3 ; Among them, AC-201 is a titanate coupling agent isopropyl tri(dioctyl pyrophosphate) titanate;

[0007] Take the In treated with the titanate coupling agent AC-201 2 O 3, initiator, surfactant, glycidyl methacrylate, deionized water, crosslinking agent and hexadecyl trimethoxysilane, react in a water bath at 60-80°C for 8-12h to obtain In-treated surface of PGMA@titanate coupling agent AC-201 2 O 3 @ Hexadecyltrimethoxysilane, which is modified In 2 O 3 .

[0008] Further scheme, in obtaining the In treated with titanate coupling agent AC-201 2 O 3 In the step, the nano-In 2 O 3 The mass ratio of AC-201, anhydrous ethanol and deionized water is (30-40):(10-16):(50-60):(90-110).

[0009] Further scheme, in obtaining modified In 2 O 3 In the step, the titanate coupling agent AC-201 is surface treated with In 2 O 3 The mass ratio of initiator, surfactant, glycidyl methacrylate, deionized water, crosslinker and hexadecyltrimethoxysilane is (30-40):(0.1-0.3):(0.2-0.4):(16-20):(60-80):(0.1-0.3):(8-12).

[0010] In a further embodiment, the initiator, surfactant and cross-linking agent described herein can be selected according to the conventional methods in the art according to actual needs. In some specific embodiments of the present invention, the initiator is ammonium persulfate; the surfactant is nonylphenol polyoxyethylene ether; and the cross-linking agent is diisopropylbenzene peroxide (DCP).

[0011] The present invention further provides a thermoplastic resin composite material, comprising 90-110 parts of a thermoplastic resin, 10-16 parts of a modified In 2 O 3 and 0.1-0.5 parts of antioxidants according to weight parts, the modified In 2 O 3 It is prepared by the preparation method described above.

[0012] Among them, the selection of thermoplastic resin is not particularly limited. Conventional thermoplastic resins in the art are suitable for the present invention. Specific examples include but are not limited to one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyamide 6 (PA6).

[0013] The antioxidant can be selected from conventional ones in the art. Specific examples include one or a mixture of two or more of tris(2,4-di-tert-butyl)phenyl phosphite (Irganox 168 for short), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (Irganox 1010 for short) and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (Irganox 1330 for short).

[0014] The present invention also provides a method for preparing the thermoplastic resin composite material as described above, comprising the following steps:

[0015] According to the ratio, thermoplastic resin and modified In 2 O 3 and an antioxidant to uniformly mix to obtain a mixture;

[0016] The mixed material is extruded and granulated through an extruder to obtain a thermoplastic resin composite material.

[0017] It is understandable that the preparation method of the thermoplastic resin composite material can adopt the conventional melt extrusion method in the art, and the specific reaction conditions, parameters, etc. can be selected according to actual needs, which will not be elaborated in detail here.

[0018] Beneficial effects of the present invention:

[0019] The present invention prepares a modified In 2 O 3 Specifically, GMA can be polymerized into PGMA. When the titanate coupling agent AC-201 is added to the surface treated In 2 O 3 When PGMA is treated with titanate coupling agent AC-201, 2 O 3 Surface deposition; Among them, the unique epoxy structure of PGMA can improve the bonding between thermoplastic resin and In 2 O 3 In addition, 2 O 3 Surface grafted AC-201 can also improve the thermal plastic resin and In 2 O 3 compatibility, all of which are beneficial to improving the mechanical properties of thermoplastic resins.

[0020] Furthermore, hexadecyltrimethoxysilane can generate a large number of Si-OH bonds after hydrolysis, which can react with In on the surface of PGMA@titanate coupling agent AC-201. 2 O 3The hydroxyl groups on the surface undergo condensation reaction to form a stable Si-O-Ti bond, transforming the linear molecular structure into a three-dimensional network cross-linked structure, and finally forming the In-treated PGMA@titanate coupling agent AC-201. 2 O 3 @ Hexadecyltrimethoxysilane, which is modified In 2 O 3 Since the microscopic bond energy of the three-dimensional network structure increases, this three-dimensional network cross-linked structure also further improves the mechanical properties of the thermoplastic resin.

[0021] The modified In prepared in the present invention 2 O 3 The prepared thermoplastic resin composite material has excellent mechanical properties. DETAILED DESCRIPTION

[0022] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. In addition, unless otherwise specified, methods that do not specifically record conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial sources.

[0024] The raw material information used in the following examples and comparative examples is as follows:

[0025] PBT (model 2002U), Polyplastics of Japan; PP (model Z30S), Maoming Petrochemical; PE (model 5070), Panjin Ethylene; PA6 (model CM1017), Toray of Japan; PET (model 008L), Aclo of Canada.

[0026] Glycidyl methacrylate, Jinan Mingwei Chemical Co., Ltd.; Nano-In 2 O 3, Shanghai Yingcheng New Materials Co., Ltd.; AC-201 (isopropyl tri(dioctyl pyrophosphate) titanate), Nanjing Aocheng Chemical Co., Ltd.; anhydrous ethanol, Shandong Taixi Chemical Co., Ltd.; deionized water, Xiamen Aoquan Environmental Protection Technology Co., Ltd.; ammonium persulfate, Shandong Chuangying Chemical Co., Ltd.; nonylphenol polyoxyethylene ether, Jinan Wangtian Chemical Co., Ltd.; diisopropylbenzene peroxide (DCP), Jiangsu Daoming Chemical Co., Ltd.; hexadecyltrimethoxysilane, Shandong Hengyu New Materials Co., Ltd.; antioxidant (model Irganox168, Irganox1010, Irganox1330), BASF.

[0027] The test conditions used in the following examples and comparative examples are:

[0028] Tensile strength: ASTM D638, the tensile specimen used is (170.0±5.0)mm×(13.0±0.5)mm×(3.2±0.2)mm, and the tensile rate is 50mm / min;

[0029] Izod notched impact strength: ASTM D256, specimen model: (125.0±5.0)mm×(13.0±0.5)mm×(3.2±0.2)mm, notch is machined, notch depth is (2.6±0.2)mm;

[0030] Flexural strength: ASTM D790, specimen size is (125.0±5.0)mm×(13.0±0.5)mm×(3.2±0.2)mm, bending rate is 1.25mm / min.

[0031] Example 1

[0032] Modified In 2 O 3 Preparation

[0033] (1) Weigh 300g of nano-In 2 O 3 , 100g AC-201, 500g anhydrous ethanol, and 900g deionized water were placed in a reaction vessel and reacted in a 40°C water bath for 10h to obtain solution A;

[0034] (2) Filter solution A, wash and dry it to obtain Indium ions treated with titanate coupling agent AC-201. 2 O 3 ;

[0035] (3) Weigh 300g of Indium ions treated with titanate coupling agent AC-201 2 O 3, 1g initiator ammonium persulfate, 2g surfactant nonylphenol polyoxyethylene ether, 160g glycidyl methacrylate, 600g deionized water, 1g crosslinking agent diisopropylbenzene peroxide (DCP), 80g hexadecyltrimethoxysilane, placed in a reaction vessel, reacted in a 60°C water bath for 8h to obtain solution B;

[0036] (4) Filter solution B, wash and dry to obtain Indium ions treated with PGMA@titanate coupling agent AC-201. 2 O 3 @ Hexadecyltrimethoxysilane, which is modified In 2 O 3 , denoted as M1.

[0037] Preparation of Thermoplastic Resin Composite Materials

[0038] (1) Weigh 90 parts of PP and 10 parts of modified In by weight. 2 O 3 M1 and 0.1 part of Irganox1010 were mixed and stirred uniformly to obtain a mixture;

[0039] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PP composite material, which is denoted as P1.

[0040] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0041] Comparative Example 1

[0042] In the preparation of the thermoplastic resin composite material in this comparative example, the In 2 O 3 Commercially available In 2 O 3 , which is the unmodified nano-In in Example 1 2 O 3 The remaining steps are the same as those in Example 1, and the specific steps are as follows:

[0043] (1) Weigh 90 parts of PP and 10 parts of commercially available In 2 O 3 , 0.1 part of Irganox1010 and stirred evenly to obtain a mixture;

[0044] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PP composite material, which is recorded as D1.

[0045] Wherein, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 230°C, the temperature of the fifth temperature zone is 230°C, the temperature of the sixth temperature zone is 230°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0046] The PP composite materials prepared in Example 1 and Comparative Example 1 were made into strips by injection molding and relevant performance tests were performed. The test results are shown in Table 1:

[0047] Table 1 Mechanical properties test results of PP composite materials in Example 1 and Comparative Example 1

[0048]

[0049]

[0050] It can be seen from the test results in Table 1 that the mechanical properties of the PP composite material in Example 1 of the present application are significantly better than those in Comparative Example 1. This is because the modified In 2 O 3 , can significantly improve In 2 O 3 It has compatibility with thermoplastic resins, and the three-dimensional network cross-linked structure it forms can further improve the mechanical properties of thermoplastic resins.

[0051] Example 2

[0052] Modified In 2 O 3 Preparation

[0053] (1) Weigh 400g of nano-In 2 O 3 , 160g AC-201, 600g anhydrous ethanol, and 1.1kg deionized water were placed in a reaction vessel and reacted in a 60°C water bath for 16h to obtain solution A;

[0054] (2) Filter solution A, wash and dry it to obtain Indium ions treated with titanate coupling agent AC-201. 2 O 3 ;

[0055] (3) Weigh 400g of Indium ions treated with titanate coupling agent AC-201 2 O 3, 3g initiator ammonium persulfate, 4g surfactant nonylphenol polyoxyethylene ether, 200g glycidyl methacrylate, 800g deionized water, 3g crosslinking agent diisopropylbenzene peroxide (DCP), 120g hexadecyltrimethoxysilane, placed in a reaction vessel, reacted in a water bath at 80°C for 12h to obtain solution B;

[0056] (4) Filter solution B, wash and dry to obtain Indium ions treated with PGMA@titanate coupling agent AC-201. 2 O 3 @ Hexadecyltrimethoxysilane, which is modified In 2 O 3 , denoted as M2.

[0057] Preparation of Thermoplastic Resin Composite Materials

[0058] (1) Weigh 110 parts of PBT and 16 parts of modified In 2 O 3 M2, 0.1 parts of antioxidant Irganox1010, 0.2 parts of antioxidant Irganox168, and 0.2 parts of antioxidant Irganox1330 are mixed and stirred uniformly to obtain a mixture;

[0059] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PBT composite material, which is denoted as P2.

[0060] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0061] Comparative Example 2

[0062] In the preparation of the thermoplastic resin composite material in this comparative example, the In 2 O 3 Commercially available In 2 O 3 , which is the unmodified nano-In in Example 2 2 O 3 The remaining steps are the same as those in Example 2, and the specific steps are as follows:

[0063] (1) Weigh 110 parts of PBT and 16 parts of commercially available In 2 O 3, 0.1 part of antioxidant Irganox1010, 0.2 part of antioxidant Irganox168, and 0.2 part of antioxidant Irganox1330 are mixed and stirred uniformly to obtain a mixture;

[0064] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PBT composite material, which is recorded as D2.

[0065] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 230°C, the temperature of the third temperature zone is 240°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 240°C, and the screw speed is 300r / min.

[0066] The PBT composite materials prepared in Example 2 and Comparative Example 2 were made into strips by injection molding machine for relevant performance tests. The test results are shown in Table 2:

[0067] Table 2 Mechanical properties test results of PBT composite materials in Example 2 and Comparative Example 2

[0068] Test items Test Standards unit P2 D2 Tensile Strength ASTM D638 MPa 66.1 58.3 Bending Strength ASTM D790 MPa 3260 2780 Izod notched impact strength ASTM D256 kJ / m2 3.9 2.6

[0069] It can be seen from the test results in Table 2 that the mechanical properties of the PBT composite material prepared in Example 2 are significantly better than those of Comparative Example 2.

[0070] Example 3

[0071] Modified In 2 O 3 Preparation

[0072] (1) Weigh 350g of nano-In 2 O 3 , 130g AC-201, 550g anhydrous ethanol, and 1.0kg deionized water were placed in a reaction vessel and reacted in a 50°C water bath for 13h to obtain solution A;

[0073] (2) Solution A is filtered, washed, and dried to obtain Indium ions treated with titanate coupling agent AC-201. 2 O 3 ;

[0074] (3) Weigh 350g of Indium ions treated with titanate coupling agent AC-201 2 O 3, 2g initiator ammonium persulfate, 3g surfactant nonylphenol polyoxyethylene ether, 180g glycidyl methacrylate, 700g deionized water, 2g crosslinking agent diisopropylbenzene peroxide (DCP), 100g hexadecyltrimethoxysilane, placed in a reaction vessel, reacted in a 70°C water bath for 10h to obtain solution B;

[0075] (4) Filter solution B, wash and dry to obtain Indium ions treated with PGMA@titanate coupling agent AC-201. 2 O 3 @ Hexadecyltrimethoxysilane, which is modified In 2 O 3 , denoted as M3.

[0076] Preparation of Thermoplastic Resin Composite Materials

[0077] (1) Weigh 100 parts of PE and 13 parts of modified In 2 O 3 M3, 0.1 parts of antioxidant Irganox168, and 0.2 parts of antioxidant Irganox1010 were mixed and stirred uniformly to obtain a mixture;

[0078] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PE composite material, which is denoted as P3.

[0079] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0080] Comparative Example 3

[0081] In the preparation of the thermoplastic resin composite material in this comparative example, the In 2 O 3 Commercially available In 2 O 3 , which is the unmodified nano-In in Example 3 2 O 3 The remaining steps are the same as those in Example 3, and the specific steps are as follows:

[0082] (1) Weigh 100 parts of PE and 13 parts of commercially available In 2 O 3 , 0.1 parts of antioxidant Irganox168, and 0.2 parts of antioxidant Irganox1010 are mixed and stirred uniformly to obtain a mixture;

[0083] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PE composite material, which is recorded as D3.

[0084] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0085] The PE composite materials prepared in Example 3 and Comparative Example 3 were made into strips by injection molding and relevant performance tests were performed. The test results are shown in Table 3:

[0086] Table 3 Mechanical properties test results of PE composite materials in Example 3 and Comparative Example 3

[0087] Test items Test Standards unit P3 D3 Tensile Strength ASTM D638 MPa 12.4 10.1 Bending Strength ASTM D790 MPa 1320 1010 Izod notched impact strength ASTM D256 kJ / m2 3.3 1.8

[0088] It can be seen from the test results in Table 3 that the mechanical properties of the PE composite material prepared in Example 3 are better than those of Comparative Example 3.

[0089] Example 4

[0090] Modified In 2 O 3 Preparation

[0091] (1) Weigh 365g of nano-In 2 O 3 , 155g AC-201, 595g anhydrous ethanol, and 1.05kg deionized water were placed in a reaction vessel and reacted in a 55°C water bath for 15h to obtain solution A;

[0092] (2) Solution A is filtered, washed, and dried to obtain Indium ions treated with titanate coupling agent AC-201. 2 O 3 ;

[0093] (3) Weigh 385g of Indium ions treated with titanate coupling agent AC-201 2 O 3 , 2.5 g initiator ammonium persulfate, 3.5 g surfactant nonylphenol polyoxyethylene ether, 195 g glycidyl methacrylate, 795 g deionized water, 2.5 g crosslinking agent diisopropylbenzene peroxide (DCP), 115 g hexadecyltrimethoxysilane, placed in a reaction vessel, reacted in a 75°C water bath for 11 hours to obtain solution B;

[0094] (4) Filter solution B, wash and dry to obtain Indium ions treated with PGMA@titanate coupling agent AC-201.2 O 3 @ Hexadecyltrimethoxysilane, which is modified In 2 O 3 , denoted as M4.

[0095] Preparation of Thermoplastic Resin Composite Materials

[0096] (1) Weigh 95 parts of PA6 and 15 parts of modified In 2 O 3 M4, 0.1 parts of antioxidant Irganox1010, and 0.2 parts of antioxidant Irganox1330 were mixed and stirred uniformly to obtain a mixture;

[0097] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PA6 composite material, which is denoted as P4.

[0098] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 320r / min.

[0099] Comparative Example 4

[0100] In the preparation of the thermoplastic resin composite material in this comparative example, the In 2 O 3 Commercially available In 2 O 3 , which is the unmodified nano-In in Example 4 2 O 3 The remaining steps are the same as those in Example 4, and the specific steps are as follows:

[0101] (1) Weigh 95 parts of PA6 and 15 parts of commercially available In 2 O 3 M4, 0.1 parts of antioxidant Irganox1010, and 0.2 parts of antioxidant Irganox1330 were mixed and stirred uniformly to obtain a mixture;

[0102] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PA6 composite material, which is recorded as D4.

[0103] The twin-screw extruder includes six temperature zones arranged in sequence. The temperature of the first temperature zone is 210°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, and the temperature of the sixth temperature zone is 260°C. The head temperature of the twin-screw extruder is 260°C and the screw speed is 320r / min.

[0104] The PA6 composite materials prepared in Example 4 and Comparative Example 4 were made into strips by injection molding machine for relevant performance tests. The test results are shown in Table 4:

[0105] Table 4 Mechanical properties test results of PA6 composite materials in Example 4 and Comparative Example 4

[0106] Test items Test Standards unit P4 D4 Tensile Strength ASTM D638 MPa 73.8 68.4 Bending Strength ASTM D790 MPa 3310 2790 Izod notched impact strength ASTM D256 kJ / m2 4.0 2.2

[0107] It can be seen from the test results in Table 4 that the mechanical properties of the PA6 composite material prepared in Example 4 are better than those in Comparative Example 4.

[0108] Example 5

[0109] Modified In 2 O 3 Preparation

[0110] (1) Weigh 375g of nano-In 2 O 3 , 145g AC-201, 585g anhydrous ethanol, and 955g deionized water were placed in a reaction vessel and reacted in a 48°C water bath for 15h to obtain solution A;

[0111] (2) Solution A is filtered, washed, and dried to obtain Indium ions treated with titanate coupling agent AC-201. 2 O 3 ;

[0112] (3) Weigh 375g of Indium ions treated with titanate coupling agent AC-201 2 O 3 , 2.8 g initiator ammonium persulfate, 3.8 g surfactant nonylphenol polyoxyethylene ether, 190 g glycidyl methacrylate, 795 g deionized water, 2.8 g crosslinking agent diisopropylbenzene peroxide (DCP), 95 g hexadecyltrimethoxysilane, placed in a reaction vessel, reacted in a 75° C. water bath for 11 h to obtain solution B;

[0113] (4) Filter solution B, wash and dry to obtain Indium ions treated with PGMA@titanate coupling agent AC-201. 2 O 3 @ Hexadecyltrimethoxysilane, which is modified In 2 O 3 , denoted as M5.

[0114] Preparation of Thermoplastic Resin Composite Materials

[0115] (1) Weigh 105 parts of PET and 14 parts of modified In 2 O 3 M5, 0.1 part of antioxidant Irganox1010, and 0.1 part of antioxidant Irganox168 were mixed and stirred uniformly to obtain a mixture;

[0116] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PET composite material, which is denoted as P5.

[0117] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0118] Comparative Example 5

[0119] In the preparation of the thermoplastic resin composite material in this comparative example, the In 2 O 3 Commercially available In 2 O 3 , which is the unmodified nano-In in Example 5 2 O 3 The remaining steps are the same as those in Example 5, and the specific steps are as follows:

[0120] (1) Weigh 105 parts of PET and 14 parts of commercially available In 2 O 3 , 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irganox168 were mixed and stirred uniformly to obtain a mixture;

[0121] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PET composite material, which is recorded as D5.

[0122] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0123] Comparative Example 6

[0124] In the preparation of the thermoplastic resin composite material in this comparative example, the In 2 O 3 In is the surface treated with titanate coupling agent AC-201 in Example 5 2 O 3 The remaining steps are the same as those in Example 5. The specific steps are as follows:

[0125] (1) Weigh 105 parts of PET and 14 parts of Indium ions treated with titanate coupling agent AC-201. 2 O 3 , 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irganox168 were mixed and stirred uniformly to obtain a mixture;

[0126] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PET composite material, which is recorded as D6.

[0127] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0128] Comparative Example 7

[0129] In the preparation of the thermoplastic resin composite material in this comparative example, the In 2 O 3 Similar to Example 5, the only difference is that no hexadecyltrimethoxysilane modification is added, that is, the modified In 2 O 3 In for the surface treatment of PGMA@titanate coupling agent AC-201 2 O 3 The remaining steps are the same as those in Example 5, and the specific steps are as follows:

[0130] (1) Weigh 105 parts of PET and 14 parts of PGMA@titanate coupling agent AC-201 surface treated In 2 O 3 , 0.1 parts of antioxidant Irganox1010 and 0.1 parts of antioxidant Irganox168 were mixed and stirred uniformly to obtain a mixture;

[0131] (2) The mixed material obtained in step (1) is extruded and granulated from a twin-screw extruder to obtain a PET composite material, which is recorded as D7.

[0132] The twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 240°C, the temperature of the second temperature zone is 280°C, the temperature of the third temperature zone is 280°C, the temperature of the fourth temperature zone is 280°C, the temperature of the fifth temperature zone is 280°C, the temperature of the sixth temperature zone is 280°C, the head temperature of the twin-screw extruder is 280°C, and the screw speed is 280r / min.

[0133] The PET composite materials prepared in Example 5 and Comparative Examples 5-7 were made into strips by injection molding machine for relevant performance tests. The test results are shown in Table 5:

[0134] Table 5 Mechanical properties test results of PET composite materials in Example 5 and Comparative Examples 5-7

[0135] Test items Test Standards unit P5 D5 D6 D7 Tensile Strength ASTM D638 MPa 64.3 59.1 61.3 62.1 Bending Strength ASTM D790 MPa 3390 2870 3050 3130 Izod notched impact strength ASTM D256 kJ / m2 4.8 2.6 3.5 3.9

[0136] It can be seen from the test results in Table 5 that the mechanical properties of the PET composite material prepared in Example 5 are significantly better than those of Comparative Examples 5-7.

[0137] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0138] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing modified In2O3, characterized in that: The following steps are involved: Nano-In2O3, AC-201, anhydrous ethanol and deionized water are reacted in a water bath at 40-60°C for 10-16h to obtain In2O3 surface-treated with titanate coupling agent AC-201; Take the In2O3 treated with the titanate coupling agent AC-201, an initiator, a surfactant, glycidyl methacrylate, deionized water, a crosslinking agent and hexadecyltrimethoxysilane, and react them in a water bath at 60-80° C. for 8-12 hours to obtain PGMA@titanate coupling agent AC-201 surface-treated In2O3@hexadecyltrimethoxysilane, which is modified In2O3.

2. The method for preparing modified In2O3 according to claim 1, characterized in that: In the step of obtaining In2O3 surface-treated with titanate coupling agent AC-201, the mass ratio of nano-In2O3, AC-201, anhydrous ethanol and deionized water is (30-40): (10-16): (50-60): (90-110).

3. The method for preparing modified In2O3 according to claim 1, characterized in that: In the step of obtaining modified In2O3, the mass ratio of In2O3 surface treated with the titanate coupling agent AC-201, initiator, surfactant, glycidyl methacrylate, deionized water, crosslinking agent, and hexadecyltrimethoxysilane is (30-40): (0.1-0.3): (0.2-0.4): (16-20): (60-80): (0.1-0.3): (8-12).

4. The method for preparing modified In2O3 according to claim 1, characterized in that: The initiator is ammonium persulfate.

5. The method for preparing modified In2O3 according to claim 1, characterized in that: The surfactant is nonylphenol polyoxyethylene ether.

6. The method for preparing modified In2O3 according to claim 1, characterized in that: The cross-linking agent is dicumyl peroxide.

7. A thermoplastic resin composite material, characterized in that: The invention is prepared from 90-110 parts of thermoplastic resin, 10-16 parts of modified In2O3 and 0.1-0.5 parts of antioxidant in parts by weight, wherein the modified In2O3 is prepared by the preparation method as described in any one of claims 1-6.

8. The thermoplastic resin composite material according to claim 7, characterized in that The thermoplastic resin is selected from one of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyamide 6 (PA6).

9. The thermoplastic resin composite material according to claim 7, characterized in that: The antioxidant is selected from one of antioxidant 168, antioxidant 1010, and antioxidant 1330, or a mixture of two or more thereof.

10. A method for preparing a thermoplastic resin composite material according to any one of claims 7 to 9, characterized in that: The following steps are involved: Thermoplastic resin, modified In2O3 and antioxidant are uniformly mixed according to a proportion to obtain a mixture; the mixture is extruded and granulated through an extruder to obtain a thermoplastic resin composite material.

Citation Information

Patent Citations

  • High-rigidity, high-toughness, heat-resistant and low-warpage conductive PBT / PCT alloy

    CN107974057A

  • Modified CeO2 filler, high-performance thermoplastic plastic containing same and preparation method of high-performance thermoplastic plastic

    CN116554709A